Asia Pasifik Memanas, Ancamankah bagi ASEAN dan Indonesia? - Armaidy Armawi; Erlan Wijatmoko (Intermestic: Journal of International Studies, 2022)
This study analyze the dynamics of security strategy in the Asia Pacific, ASEAN countries and Indonesia. There is a competition which illustrates Cohen's theory four pillars of power that influences the transformation of the geopolitical architecture of defense and security between the US and China. This study used descriptive and synthesis methods, which meant a combination of systematic thinking patterns and a problem description. Through this research, it can be concluded that, first, there is a transformation of the geopolitical architecture of defense and security in the Asia Pacific region. Second, the dispute between China with Vietnam, Philippines, Malaysia and Brunei Darussalam in the South China Sea has potential for natural resources and global economic interests. Third, the dispute in the South China Sea has led to a potential security escalation in Indonesia's maritime area. For this reason, Indonesia should enhance its Naval Power to build Indonesia's maritime security.